UPAYA PENINGKATAN PENDAPATAN USAHA MELALUI KREDIT USAH PADA SEKTOR UMKM - Lestari, Elly; Setyawati, Yuni; Valentina Meli, Faustina (Unitri Press, 2023)
The researcch objective wass to determine the effecct of business credit in an effort to increase MSME sector business income around Tribhuwana Tunggadewi University, Malang City. Thiis research method is a quantitatiive method. The researchh instrument uses a questionnairee. The data collection technique was purposive sampling with 30 respondents as MSME managers or owners. The data analysis techniquee is Simple Linear.Regression. Based onthe resultsof the study that Business.Credit has. a. posiitive and significant. influence. on MSME business. iincome. This means that the greater the provision of busiiness loans and the proper use of them will increasee the income of MSME businesses. The business credit contribution to operating income is 96.5%. Increasing business income will encourage the business to grow even more.